erencanaan Penanganan Kawasan Pemukiman Kumuh Di Kelurahan Tanjung Tiram Kabupaten Batubara - Hasrul Rizka; Agus Purwoko; Rujiman Rujiman (Fakultas Teknik, 2018)
The problem of urban slums was often one of the main issues that is quite polemic, thus never overtaken by the handling efforts from time to time. Particularly, the impact of slum settlements will also lead to a bad paradigm for the administration of the government. The Problem of Slum Settlement was also experienced by the Batubara District, especially in Kelurahan Tanjung Tiram, TanjungTiram Sub-district. The aim of this research is to identify the physical condition of slumsettlement, analyze the slum level of settlement and analyze the planning of handling. This research was a descriptive study of qualitative analysis in which researcher describes the phenomenon, which exists by analyzing and presenting the facts systematically to facilitate understanding and drawing conclusions. Based on the result of the research, it is concluded that the physical condition of slum settlement need improvement and rearrangement, the result of analysis for slum level of settlement in Tanjung Tiram sub-district is medium slum, and the result of analysis for handling planning is model of village improvement program (KIP).